Urgensi Pengaturan Hukum Kepailitan Transnasional Kawasan Association of Southeast Asian Nations - Mochamad Cholil (Media Iuris, 2023)
AbstractThe development of transnational business has had an impact on the emergence of international business transactions in which it is possible for legal subjects to own assets, both in the form of assets and liabilities in several countries. One area of law related to international business transactions is transnational bankruptcy law. The importance of regulating transnational bankruptcy law as a solution that can resolve various problems of transnational bankruptcy law has made many countries wish to form an international agreement that specifically regulates transnational bankruptcy, including the regional organization of the Association of Southeast Asian Nations or better known as ASEAN. So that the existence of transnational bankruptcy law arrangements in the ASEAN region is needed to resolve bankruptcy cases involving every ASEAN member country in it. This research is legal research using several problem approaches, namely statutory approaches, comparative approaches, and conceptual approaches. The results of this study indicate that ASEAN Cross Border Insolvency can be formed immediately as a bankruptcy regulation in the ASEAN region to ensure legal certainty for the parties. AbstrakPerkembangan bisnis transnasional telah berdampak terhadap adanya transaksi bisnis internasional di mana dimungkinkannya bagi subjek hukum dimilikinya harta kekayaan, berupa aktiva serta pasiva pada beberapa negara. Termasuk bidang hukum berkaitan dengan transaksi bisnis internasional, yakni perihal hukum kepailitan transnasional. Pentingnya pengaturan hukum kepailitan tranasional sebagai sebuah solusi yang dapat menyelasikan beragam permasalah hukum kepailitan transnasional, menjadikan kebanyakan negara berharap suapaya dibentuknya suatu perjanjian internasional khususnya aturan kepailitan transnasional, tidak terkecuali organisasi regional Perhimpunan Bangsa-Bangsa Asia Tenggara atau yang lebih dikenal ASEAN. Sehingga adanya pengaturan hukum kepailitan transnasional kawasan ASEAN sangatlah dibutuhkan guna menyelesaikan perkara kepailitan yang melibatkan setiap negara anggota ASEAN di dalamnya. Penelitian ini adalah penelitian hukum dengan menggunakan beberapa pendekatan masalah, yakni pendekatan perundang-undangan, pendekatan perbandingan, serta pendekatan konseptual. Hasil penelitian ini menunjukkan agar dapat segera terbentuknya ASEAN Cross Border Insolvency sebagai regulasi kepailitan kawasan ASEAN guna menjamin kepastian hukum bagi para pihak.